2001
DOI: 10.1074/jbc.m108811200
|View full text |Cite
|
Sign up to set email alerts
|

All Phox Homology (PX) Domains from Saccharomyces cerevisiae Specifically Recognize Phosphatidylinositol 3-Phosphate

Abstract: Phox homology (PX) domains are named for a 130-amino acid region of homology shared with part of two components of the phagocyte NADPH oxidase (phox) complex. They are found in proteins involved in vesicular trafficking, protein sorting, and lipid modification. It was recently reported that certain PX domains specifically recognize phosphatidylinositol 3-phosphate (PtdIns-3-P) and drive recruitment of their host proteins to the cytoplasmic leaflet of endosomal and/or vacuolar membranes where this phosphoinosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(189 citation statements)
references
References 37 publications
3
185
1
Order By: Relevance
“…It should therefore only be used as a first-pass to determine whether binding to phosphoinositides (or other lipids) can be detected at all. As described in our genome-wide analyses of S. cerevisiae PH and PX domains [26,27], we have often detected phosphoinositide binding using this method that is too weak to be measured by any of the more quantitative approaches outlined later in this article. Other laboratories have reported similar findings [28].…”
Section: Fat Blots/dot-blots/lipid Westerns For Analyzing Binding To mentioning
confidence: 99%
See 2 more Smart Citations
“…It should therefore only be used as a first-pass to determine whether binding to phosphoinositides (or other lipids) can be detected at all. As described in our genome-wide analyses of S. cerevisiae PH and PX domains [26,27], we have often detected phosphoinositide binding using this method that is too weak to be measured by any of the more quantitative approaches outlined later in this article. Other laboratories have reported similar findings [28].…”
Section: Fat Blots/dot-blots/lipid Westerns For Analyzing Binding To mentioning
confidence: 99%
“…First, the state of the phosphoinositides in the spots on the nitrocellulose filter is far from representative of that found in vivo. Second, experience has shown that in many cases phosphoinositide binding that appears robust in dot-blots cannot be detected using any of the other commonly used approaches to study lipid binding [26][27][28]. Conversely, the examples of dynamin's PH domain [31][32][33] and the PH domains from S. cerevisiae proteins Ynl047cp and Yil105cp [27,34] illustrate that phosphoinositide binding that is very weak (and only detectable with dot-blots) can nonetheless be physiologically relevant.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface plasmon resonance experiments were performed as described (32). Dioleoylphosphatidylcholine vesicles lacking or containing 3% (mol/mol) PI3P, PI4P, PI4,5P2, or PI3,5P2 were prepared and immobilized onto an L1 sensor chip using a Biacore X instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Boi1 PH domain point mutants impaired in PI4,5P2 binding fail to function or localize to the bud cortex (31). The Cdc42 scaffold protein Bem1 possesses a phox homology domain that binds phosphatidylinositol 3-phosphate (PI3P (32)), which has a prominent role in protein trafficking to the vacuole (24).…”
mentioning
confidence: 99%